Housing, taxation and subsidies : a study of housing in the United Kingdom - Nevitt, Adela Adam. (London : Nelson, 1966)
This book deals with British housing law which control their occupation and the town planning law which control their location
Includes bibliographical footnotes and index.
oo 25/10/2018
Loans
Keywords: Housing; United Kingdom